(3OjhGf HGMSfs - (3YHO Gddg Hf eMeO HGMSf Led Gddjd,J (B1347 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg Hbhdg (B: (3CSJZaQ Gddg ef PfHi hEUQGQi CSJZaQ Gddg ef LQei hChRGQi s
(3BNQgG (B:s
(3jfJgi GdehLhO efg Hbhdg (B: (3eY GdBd hGdCUMGH eG bGdgG aJi CQGc HYjf GdaVd CfJ HgG CMQi s
(3HgG fXGe GdJYbjHIs
(3cJHJ YfGhjfgG HGdMeQIs
(3jdjgG hQbJGf bjd CfgeG HNW GdTGYQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs